Adaptation of the Indonesian quality of life-5 questionnaire - Widwi Mukhabibah; Hery Susanto (University of Muhammadiyah Malang, 2022)
The QoL5 questionnaire is five items self-report to measure the quality of life, based on the integrated quality of life (IQOL) theory by S. Ventegodt. The validation test aims to determine the psychometric properties of the questionnaire. The translation and adaptation stages are carried out based on the International Test Committee (ITC) manual. The sample consisted of 217 people obtained a convenience sampling. Data analysis showed that the questionnaire was reliable (α=.78). Item discrimination ranges from .41-.74 (very good item). Confirmatory factor analysis (CFA) shows that the unidimensional model QoL5 has a good fit to the data (RMSEA=.07, CFI=.99, and SRMR=.05). The factor loading significance test shows a value of .5 or above means all items are valid. Tests of content validity (CVI=.87), convergent validity (AVE=.55), and criterion validity (r=.399-.581) showed that all items were valid. The results of the analysis indicate that the QoL5 questionnaire is a reliable and valid instrument for measuring the quality of life.